(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Papilledema is the passive non-inflammatory swelling of the optic nerve head associated with increased intra cranial pressure. Papilledema is seen in many causes of increased intra cranial pressure. Papilledema is one of the earliest signs in cases of increased intra cranial pressure. It is important to determine the ability to identify papilledema at the earliest and classify it appropriately, which could account for early diagnosis of increased intracranial pressure in patients presenting in hospital with subtle signs and with non-invasive techniques available in a tertiary care setup. Materials and Methods: A cross-sectional study was done including patients clinically diagnosed with papilledema. History and general examinations will be done which is followed by complete ocular examinations and Neurological examination. OCT will be done to evaluate the thickness of the peripapillary retinal nerve fibre layer. Patients diagnosed with papilledema are subjected to MRI brain with or without MRV. Further LP is advised only for therapeutic or diagnostic purposes as per the advice of a neurologist. Results: The history suggested that more common presenting symptom of all the patients was a headache. Majority of patients presented with papilledema were diagnosed with idiopathic intracranial hypertension. Based on the study no strong correlation could be assigned on the involvement of the 6th cranial nerve. The association of visual acuity and the clinical classification of papilledema. OCT, RNFL thickness had a good association with the different clinical classifications of papilledema with a p-value less than 0.001. MRI optic nerve sheath diameter didn’t show a significant association with the classification of papilledema. Posterior scleral angle and optic nerve tortuosity also didn’t show much significant association with the classification of papilledema. Conclusion: Early and accurate diagnosis of papilledema is always an important aspect in clinical practice, for early initiation of treatment of intracranial pressure, and also to monitor the progression of papilledema. Based on the study, the early assessment of papilledema and the high prevalence of causes based on the statistics causes could be assessed. Based on the study, OCT values showed a strong correlation with diagnosing papilledema. And a strong association was observed with the different classifications of papilledema.